Strategic planning in risk-based quality improvement at Universitas Brawijaya - Dwi Cahyani, Okik; Sholihah, Qomariyatus; Haryono, Bambang Santoso (Wacana Journal of Social and Humanity Studies, 2026)
Objective: Strategic planning is a plan drawn up to achieve an organization’s objectives within a specific timeframe, whether short-, medium-, or long-term. Improving the quality of education requires a strategy. The focus of the research is strategic planning for risk-based quality improvement at Universitas Brawijaya, utilizing the theory proposed by Choirunisa, D (2019), namely: Firstly, 1) Development of vision, mission, and objectives, 2) Identification of external and internal factors (SWOT analysis), 3) Short-term, medium-term, and long-term planning, 4) Determination of winning strategies. Second, the supporting and hindering factors. Design/Methods/Approach: This study employs a descriptive, qualitative research design. Findings: The results of this study are as follows: Firstly, 1) The development of the vision, mission, and objectives is in line with the vision, mission, and Strategic Plan (RENSTRA) of Universitas Brawijaya. 2) In the SWOT analysis, Universitas Brawijaya and the Quality Assurance Agency do not treat threats as obstacles, but rather as challenges. 3) Short-term planning, namely the RKAP (Work Plan and Budget), covers a period of one year. Medium-term planning consists of the Strategic Plan (RENSTRA) covering a five-year period. Long-term planning consists of the Long-Term Master Plan (RIP). 4) The Quality Assurance Agency at Universitas Brawijaya has formulated a risk-based quality standard. Secondly, a supporting factor is that the Quality Assurance Agency possesses human resources who are experts in their respective fields. Originality/Value: This study offers a unique empirical perspective on reframing traditional SWOT analysis into a SWOC (Challenges rather than Threats) approach to foster a more proactive organizational mindset. Practical/Policy implication: University performance management through the SAKIP system requires the Strategic Plan (RENSTRA) to be a mandatory document and serves as an overarching framework for Universitas Brawijaya's subordinate units. Meanwhile, the inhibiting factor is the existence of national policies that are counterproductive to Universitas Brawijaya.   Keywords: Strategic planning; quality; risk-based; higher education; SWOC analysis JEL Classification:             I23; M10; I28